Optical properties of In0.5Ga0.5As/GaAs quantum dots grown by heterogeneous droplet epitaxy with post-growth annealing - Lee, CM; Noh, SK; Lee, JI; Lee, DH; Leem, JY; Han, IK; Mano, T; Koguchi, N (KOREAN PHYSICAL SOC, 2002)
e have examined the effect of thermally induced interdiffusion on the photoluminescence (PL) emission of In0.5Ga0.5As quantum dots grown on GaAs substrates by using heterogeneous droplet epitaxy. Thermal intermixing was found to result in significant blue-shifts of the PL emission at annealing temperatures up to 800 C and in a decrease of the intersublevel (E-01 = E-1 - E-0) by se much as 22.7 meV. In addition, the inhomogeneously broad linewidth of the PL spectra became more narrow with increasing annealing temperature. These results can be explained by the interdiffusion of In-Ga atoms, which changes the composition of the QDs, at the interface between the QDs and the GaAs barrier.
Keywords: LUMINESCENCE; ISLANDS; INGAAS